Landscape change in the Levuvhu and Nzhelele River catchments, Venda Limpopo Province South Africa. Issue 1 (March 2020) - Vessal, Ali; Musakwa, Walter; Malapane, Olgah Lerato
Abstract: Little is known regarding landscape change, although the factors and implications of such changes are evident each day. Over the past decades rapid urban sprawl, urban land expansion, agricultural intensification and expansion of renewable energy use has had a negative impact on the environment and puts the sustainability of land at risk. This paper seeks to provide knowledge on global environmental change, landscape change and climate change and to identify the drives of landscape change and their implications. Moreover, the research study aims to provide data on the drivers that influence landscape change. It seeks to provide information on how land use change and landscape change in rural areas can be affected by factors such as urbanization, climate change and human activities (rivers, agriculture, deforestation and so forth). The study shall be focused on the Levuvhu and Nzhelele river catchment area, located within the Venda Region of the Limpopo Province in South Africa. Group focus discussions, field work and interviews were conducted to collect data with environmental, geography, landscape surveyors and the local ordinary residents within the areas. The results of the findings were assessed accordingly and provided to give a clear understanding of the importance of landscape change.